Making Method of Sea Squirt Skin Powder and the Powder made thereby - CHA, SUN KIL; GONG, CHUNG SIK (2020)
The present invention relates to a method for manufacturing sea squirt shell powder and, more specifically, to a method for manufacturing sea squirt shell powder which efficiently removes salt of sea squirt shells which are not easy to remove salt therefrom and reduces a drying time, thereby being beneficial in terms of hygiene and maintaining freshness. The method comprises: a step (S1) of cleanly washing sea squirt shells and dehydrating water therefrom; a step (S2) of putting the dehydrated sea squirt shells of the step (S1) into water, and boiling the same at 100°C for 5-7 minutes; a step (S3) of washing the boiled sea squirt shells of the step (S2) with fresh water and dehydrating the same; a step (S4) of hot-air drying the dehydrated sea squirt shells of the step (S3) at a temperature of 60-80°C for 3-5 hours; a step (S5) of drying the hot-air dried sea squirt shells of the step (S4) at a temperature of 25°C for 6-8 hours by a cold air drying method; and a step (S6) of pulverizing the cold-air dried sea squirt shells of the step (S5) with a food grinder. 본 발명은 멍게 껍질 분말을 제조하는 방법에 관한 것으서, 보다 구체적으로는 염분을 제거하기 쉽지 않은 멍게 껍질의 염분을 효과적으로 제거하고, 건조시간을 단축하도록 하여, 위생면과 선도유지에 유익한 멍게 껍질 분말의 제조하는 방법에 관한 것이다. 멍게껍질을 깨끗이 세척하여 물기를 탈수하는 단계(S1); 상기 S1 단계의 탈수된 멍게 껍질을 물에 넣고 100℃에서 5 ~ 7분간 자숙하는 단계(S2); 상기 S2 단계의 자숙한 멍게껍질을 담수로 세척하고 물기를 탈수하는 단계(S3); 상기 S3 단계의 탈수된 멍게껍질을 60 ~ 80℃의 온도로 3 ~ 5시간 열풍 건조하는 단계(S4); 상기 S4 단계의 열풍 건조된 멍게 껍질을 25℃에서 6~ 8시간 냉풍 건조방법으로 건조시키는 단계(S5); 및 상기 S5 단계의 냉풍 건조된 멍게 껍질을 식품분쇄기로 분말화하는 단계(S6)을 포함하는 것을 특징으로 한다.